Current status of the intercultural opening at hospitals and rehabilitation centres for psychosomatic medicine and psychotherapy in Bavaria - Weber, Alexander; Erim, Yesim; Georgiadou, Ekaterini (Zeitschrift für Psychosomatische Medizin und Psychotherapie, 2019)
Objectives: Intercultural opening of the health care system is supposed to optimize health services for migrants. It is part of the National Integration Plan and promoted by medical societies in Germany. This study examines its state of implementation at hospitals and rehabilitation centres for psychosomatic medicine and psychotherapy in Bavaria.
CRIS-Team WoS Importer:2020-03-17

Current status of the intercultural opening at hospitals and rehabilitation centres for psychosomatic medicine and psychotherapy in Bavaria. - Weber, Alexander; Erim, Yesim; Georgiadou, Ekaterini (Zeitschrift für Psychosomatische Medizin und Psychotherapie, 2020)
Objectives: Intercultural opening of the health care system is supposed to optimize health services for migrants. It is part of the National Integration Plan and promoted by medical societies in Germany. This study examines its state of implementation at hospitals and rehabilitation centres for psychosomatic medicine and psychotherapy in Bavaria. Methods: A written survey was conducted using a modified version of the questionnaire for the implementation of intercultural opening in the mental health care system IKÖ-P (Penka et al. 2012a). Results: Altogether 18 institutions responded. Migrants were underrepresented among patients and employees excluding physicians. Specialized psychotherapeutic interventions for migrants were rarely available, but frequently used when offered. Conclusions: Intercultural opening was poorly implemented in a structural level. Due to the low response-rate of 21.7 % the survey is not representative. Participation of institutions interested in intercultural opening could have led to biased results. To provide adequate psychosomatic medical care for migrants, intercultural opening should be further developed.
EVALuna2:421126